Micro Device Modeling Method and Design for Manufacturability - Zheng Liu; Bo Sun (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The micro device designing flow begins with the mask design currently, which is not intuitive for designer and sometime made them confused. As a result, the manufacturability is hard to prove in advance with the traditional designing way. Especially for surface micro-machined device with multiple structural layers, the 2D mask design cannot ensure the fabrication of complex 3D device with high yields reliably. The rise of structural designing strategies gave a direction to change the traditional habit. On the other hand, the top-down method provides the advanced designing flow, which begins with the system level design. However, there still some key technologies to study further because of the novel design procedure. To improve the manufacturability of micro device, the designing flow based on design for manufacturability methodology is presented, which draw on the advantages and experience of the mechanical design method. The key technologies on the structural design level, the processes planning level and the fabricating level are introduced correspondingly. In addition, we present the framework to implement the method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3081